Poor immunological recovery among severely immunosuppressed antiretroviral therapy-naïve Ugandans - Nanzigu, Sarah; Kiguba, Ronald; Kabanda, Joseph; Mukonzo, Jackson K .; Waako, Paul; Kityo, Cissy; Makumbi, Fred (HIV/AIDS – Research and Palliative Care, 2013)
With access to antiretroviral therapy (ART) expanding in resource-limited settings, assessing factors related to clinical, immunological, and virological outcomes of ART is of great importance. Even though ART is loosely referred to as a lifelong treatment, clinical, immunological and virological outcome measures differ among patients on highly active ART (HAART), with differences reported within and across cohorts.1–6 Mortality is among the ART-outcome variables that have been studied extensively, and rates of up to 30% have been reported during the first year of treatment in some sub-Saharan settings
Keywords: Baseline CD4 cells; HIV severity; Immunological recovery; ART outcome; ART